The Social and Cultural Impact of Marine Tourism on Coastal Communities: A Qualitative Study at Tanjung Lesung Beach - Baihaqi, Faqih; Annida, Shafira Bilqis (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the social and cultural impacts of marine tourism on coastal communities in Tanjung Lesung Beach through a qualitative approach. In-depth interviews and observations were conducted to understand changes in social structure, cultural values, and community interactions due to tourism development. The results show that tourism provides positive economic impacts for the community but also triggers changes in local cultural values and social interaction patterns. However, there are community efforts to balance economic benefits and cultural preservation. This research recommends a more sustainable and inclusive approach to tourism to maintain the balance between local culture and tourism.